2015
DOI: 10.1111/aej.12127
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fracture resistance of endodontically treated teeth restored with composite resin along with fibre insertion in different positions in vitro

Abstract: This study was carried out to compare the different techniques of placement of polyethylene fibre (Ribbond) on reinforcement of endodontically treated teeth with MOD cavities in vitro. Forty extracted human premolars were randomly assigned to four groups (n = 10). Teeth in Groups I-IV received root canal treatment and a MOD cavity preparation, with gingival cavosurface margin 1.5 mm in coronal to cementoenamel junction. Group I served as no fibre group, Group II as occlusal fibre group, Group III as base fibre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
12
0
2
Order By: Relevance
“…Root-filled teeth are exposed to heavy masticatory loading forces. However, there is no consensus about the best restoration type of root-filled posterior teeth [ 3 7 ]. Treatment options to reinforce the residual tooth structure include composites, fiber reinforced composites, glass ionomer cement, and, if required, post and core restoration and crowns (full metal or porcelain-fused to metal crowns) [ 5 , 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Root-filled teeth are exposed to heavy masticatory loading forces. However, there is no consensus about the best restoration type of root-filled posterior teeth [ 3 7 ]. Treatment options to reinforce the residual tooth structure include composites, fiber reinforced composites, glass ionomer cement, and, if required, post and core restoration and crowns (full metal or porcelain-fused to metal crowns) [ 5 , 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of fiber-inserted composite restorations with different positions has been investigated with the goal of increasing the fracture strength of endodontically treated teeth [ 5 , 7 ]. Belli et al [ 2 ] reported that the use of polyethylene fibers under the composite restoration increases the fracture resistance of root canal filled teeth with mesio-occluso-distal (MOD) preparation.…”
Section: Introductionmentioning
confidence: 99%
“…1 Direnci artan restorasyonlarla birlikte, destek oldukları diş dokularının desteğinin de arttığı göz önünde bulundurularak, kompozit reçinelerde meydana gelen bu başarısızlıkların azaltılması için, restorasyonlar ile birlikte fiber ağların kullanılması tavsiye edilmektedir. [4][5][6][7][8]20,22,23 Örneklerin standart hâle getirilmesini mümkün kılmak, yani deneylerde standardizasyonu sağlamak için, kompozit reçine ve fiber ağ uygulamalarının, diş sert dokularının desteği olmaksızın model kalıpları üzerinde kavite ölçülerine uygun olacak şekilde hazırlanması planlanmıştır. 24 Bu sayede, farklı şekillerde ve konfigürasyonlarda yerleştirilmiş fiber ağların, kompozitin basınç kuvvet lerine dayanımına etkilerinin hiçbir ilave parametre olmaksızın, net bir şekilde değerlendirilmesi amaçlanmıştır.…”
Section: Discussionunclassified
“…Fiber ağlar ile desteklenen ya da desteklenmeyen kompozit restorasyonların uygulandığı dişlerin, bu uygulama sonrası basınç kuvvetlerine karşı direncini inceleyen birçok çalışma yapılmıştır. [16][17][18][19][20]23,[25][26][27][28][29] Bunların yanı sıra fiber ağlar ile desteklenen kompozit reçinelerin bükme dirençlerini inceleyen çalışmalar da bulunmaktadır. 30,31 Ancak, yapılan çalışmalar incelendiğinde, kompozit reçineler içine, fiber ağların farklı şekillerde yerleştirilmesi sonrasında, diş dokuları olmaksızın sadece restorasyonların basınç kuvvetlerine karşı yapısal dirençlerini inceleyen herhangi bir çalışmaya rastlanmamıştır.…”
Section: Discussionunclassified
“…It is also known that the clinical applicability of GFP is directly related to the reconstruction of the dental element lost (MAKADE et al, 2011;AMBICA et al, 2013;WANDSCHER et al, 2014;REZAEI et al, 2015;RAHMAN et al, 2016). Thus, an intraradicular post should be selected with caution, verifying the amount of remaining tooth structure, root canal anatomy, post length and diameter, as well as the physical properties and modulus of elasticity (ALOMARI et al, 2011;HATTA et al, 2011;LE BELL-RÖNNLÖF et al, 2011).…”
Section: Introductionmentioning
confidence: 99%